Anne of Avonlea - Montgomery, L. M. (Lucy Maud), 1874-1942. (New York Scholastic Inc., 2002)
In this sequel to Anne of Green Gables, the engaging orphan, just "half-past sixteen," becomes a schoolma'am in a small village on Prince Edward Island.
Keywords: Orphans -- Fiction; Teachers -- Fiction; Islands -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Canada -- History -- 1867-1914 -- Fiction